Systematic Review of Lean Management: Hospital Transformation for Increasing Operational Efficiency and Patient Care - Putri Ayu Nurhaliza; Muhammad Pandu Aditya; Adinda Intan Pratiwi; Monica Aprilla Andestri; Elvara Angelita; Asmaripa Ainy (Universitas Widya Gama Mahakam Samarinda, 2024)
Background: One of places that providing health services is a hospital which provides comprehensive health services. Therefore, one of the benchmarks that hospitals facing is to always maintain consumer trust by improving quality of services so that consumers’ satisfaction significantly increases. In this research, Lean Management has become a more popular approach in various industries including the health sector such as hospitals. Objectives: To learn about lean management in hospitals such as how to implement lean management and find out the efficiency of lean management in hospitals. Research Method: A systematic review that used a qualitative meta-synthesis approach based on the results of similar studies. Results: The impacts of lean management on the quality of hospital’s health services were found. Conclusion: The context of transformation for the hospital. Implementing lean management has a significant impact on various aspects, from operational efficiency to service quality. Applying its management allows hospitals to proactively identify areas where improvement is needed, thereby ensuring that high standards of services are maintained.